(NoTELLO LIRI^ESKAQ DRAMA W (B4-(NH DESTWIQH(B.s (NLIBRETTO a(B.(NbOJTO s - (NdVUZEPPE wERDIs; (Na(B.(NbOJTAs (NPEREWOD^IKs ((NmOSKWA s (NlANXs (NpLANETA MUZYKIs, 2016)
"(NoTELLO(B"((NITAL(B.(NoTELLO(B)-(NOPERA dVUZEPPE wERDI (B4-(NH DEJSTWIQH NA LIBRETTO aRRIGO bOJTO PO MOTIWAM ODNOIMENNOJ PXESY {EKSPIRA(B.s
Keywords: (NLIBRETTOs